The lentil : botany, production and uses - Erskine, William (CABI, 2009)
The lentil is a crop primarily grown in the developing world. It has the ability to use water efficiently and grow in marginal environments as well as being high in protein. This title includes chapters that outline improvements in production, such as water and soil nutrient management, agronomy, mechanization, and weed management.